Effect of the geographical origin on the starvation, desiccation tolerance and metabolite content in Anastrepha fraterculus adults = Efecto del origen geográfico en la tolerancia a la inanición, desecación y contenido de metabolitos en adultos de Anastrepha fraterculus - Fernández, Fátima Liliana (2025)
Climate significantly influences the geographic distribution of species. Understanding how species adapt to climatic stressors often involves analysing phenotypic variability across different regions. Insects exhibit diverse strategies to cope with environmental challenges; among these, the accumulation and use of metabolic reserves play a pivotal role in enhancing tolerance to stress. Anastrepha fraterculus is a major fruit pest in South America. Despite the significant progress achieved in the study of many biological traits, this fly's ability to withstand climatic stress has not been analysed yet. The present study examines the tolerance of A. fraterculus to starvation and desiccation in adult flies derived from diverse geographical origins. It also explores the role of metabolic reserves in stress tolerance. Wild flies from five geographic locations in Argentina were reared until F9 from F1 on mango (Mangifera indica) under laboratory conditions. Starvation and desiccation tolerance were evaluated in both sexes and in sexually immature and mature flies. Protein, lipid and glycogen levels were quantified to assess their association with stress tolerance. Significant differences in adult longevity and nutritional metabolite levels under starvation and desiccation stresses were observed between flies derived from different geographical areas. However, no clear correlation was found between nutrient content and stress tolerance. These findings suggest that, beyond physiological traits, local environmental conditions may have shaped population-specific adaptive responses, as documented in other insect species. The observed variability highlights the potential role of small-scale environmental heterogeneity in enhancing adaptive capacity. This study provides a foundation for understanding the interplay between metabolic reserves, environmental history and physiological mechanisms underlying stress tolerance in A. fraterculus.